Analysis of Exchange Rate and Inflation in Indonesia Under Floating Exchange Rate System - Yollit Permata Sari; Urmatul Uska Akbar; Isra Yeni; Hari Setia Putra; Dwi Rani Puspa Artha (Universitas Negeri Semarang, 2023)
Changes in the exchange rate system in Indonesia from a fixed exchange rate system to a floating exchange rate system have caused the exchange rate in Indonesia to fluctuate very easily. This study aims to analyze the effect of the exchange rate on inflation or what is known as the exchange rate pass through. This study used monthly data from January 2016 to December 2021. The data in this study were obtained from the world bank and Bank Indonesia. This study used a multiple linear regression model. The dependent variable is inflation, while the independent variable is the exchange rate. This study also uses a control variable to prevent biased results. The control variables are the Wholesale Price Index, the number of shares traded and the amount of money in circulation or money supply. The results of the study found that the exchange rate did not affect inflation in Indonesia. Meanwhile, for the control variable, the same results were found in the variable money supply, which also did not significantly affect inflation. Different results were found in the wholesale price index and the number of shares traded which significantly affected inflation respectively. The conclusion shows that when Indonesia adopts a floating exchange rate system, exchange rate changes are not significant in influencing inflation.